IMPROVING THE PROFESSIONAL COMPETENCE OF TEACHERS IN EDUCATION OF VALUE ATTITUDES TOWARD HUMANITY IN YOUNGER SCHOOL STUDENTS - Tretiak, Olha (European Science, 2023)
The study reveals the peculiarities of improving the professional competence of teachers and modern scientific approaches in the education of a valuable attitude towards a person in younger schoolchildren. The high demands on the modern teacher are determ